An exploration of advertising values and beauty ideals manifest in print advertisements of cosmetic brands: A content analysis of Boots No.7 - Gong, Yu-Qing (2017)
With the development of business, technology, science and globalization, the cosmetic market all over the world has become larger and potential. The robust growth of the sales of cosmetic in UK cannot be ignored. Advertisements are considerably important for the promotion of products, and advertising values and beauty ideals are two important factors included in the advertisements, especially for the cosmetics advertisements. Many previous studies did researches into advertising values and beauty ideals respectively, but there were few studies aiming to study the interrelationship between advertising values and beauty ideals.